Clinical echocardiography - Henein, Michael Y. (Springer London, 2012)
Echocardiography is the cornerstone of the practice of cardiology. It is used for outpatient clinics, on wards to assess patient progress and in cath labs and theatres to guide interventional procedures, device implantation and complex surgery. Yet few busy cardiologists have the time to embrace the fast-developing technology in this field and to implement in their clinical practice. Clinical echocardiography, now in a completely revised second edition, is a book that will take all the stress out of looking at an echocardiogram and assessing exactly what is occurring in the patient's heart. This book, with its many images of almost every cardiological condition, will provide an instantaneous interpretation of the image on the screen, guiding the cardiologist through the detailed diagnostic and therapeutic steps to achieve optimum patient management and aiding the interventionist and surgeon as they carry out the necessary procedures. The book also contains up-to-date findings and summaries of academic knowledge of echocardiography, providing a useful resource for academics and researchers and suggesting ideas for further investigation.